ILLUMINATION OF THE PROBLEM OF DIRECTINGTO PROFESSIONS YOUTH IN THE HERITAGE OF MEDIEVAL SCIENTISTS AND ENCYCLOPEDISTS - Shodiyev N; S.Saydullayev, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article is being considered the rich heritage of the learned encyclopedists of Mavorounnahr on the choice of profession of the young generation.